Embates da fé : católicos e protestantes no Recife, 1860-1880 - Santana, Jair Gomes de (2007)
This work aimed to understand the social problems involving Catholicism and Protestantism, during the 1860s and 1880s, in Recife. We ve observed all the speeches presented in newspapers by that time,specially in Jornal do Recife and O Cathólico. This study considered the social, economical, political and cultural events in Brazil and in around the world, in the second half of the 19 th century. These changes made the religious practice become weak in Brazil, forcing it to change its model to the ultramontane. The attempt to make the popular Catholicism become an ultramontane model didn t succeed and most people were taken to the Protestant universe. In Pernambuco (1842) a Negro Protestantism rose because of a Protestant group called Divino Mestre . That movement had a negro as their leader, and he taught his followers how to read also rejected the Catholic tradition. All the local Protestantism feared him. The government was afraid of a rebellion similar to the Malês in Bahia or another like the one in Haiti. The missionary Protestantism didn t threaten the local economy and the social bases, so it was welcomed by the masons and liberals. However, the Protestant missionary s activity developed among, half-blood people and Negroes. All the incidents involving faith, which were studied here, were in the media, in newspapers. Protestants used the polemic presented by newspapers as strategies to occupy institutional spaces to which they didn t have access before. This way, they got the support of those who were against the Church and took advantage of the situation provided by the Religious matter in the Empire